Using primary care-based paper and telephone interventions to increase uptake of bowel scope screening in Yorkshire: a protocol of a randomised controlled trial. Issue 7 (28th July 2018) - McGregor, Lesley M; Kerrison, Robert S; Green, Trish; Macleod, Una; Hughes, Mark; Gibbins, Monica; Morris, Stephen; Rees, Colin; von Wagner, Christian
Abstract : Introduction: Evidence suggests bowel scope screening (BSS) can significantly reduce an individual's risk of developing colorectal cancer (CRC). BSS for 55 year olds was therefore introduced to the English Bowel Cancer Screening Programme (BCSP) in 2013. However, the benefits are only gained from test completion and uptake is low (43%). Primary care involvement has consistently shown benefits to cancer screening uptake and so this study aims to build on this knowledge and evaluate general practitioner (GP) practice led interventions designed to increase BSS attendance. Methods and analysis: A three-arm randomised controlled trial will be conducted to evaluate three interventions: one intervention for prospective BSS invitees (primer letter with locally tailored leaflet sent by an individual's GP practice) and two interventions for those who do not attend their BSS appointment (a self-referral letter sent by an individual's GP practice and a patient navigation call made on behalf of an individual's GP practice). The trial will be set in Yorkshire. Individuals soon to receive their invitation to attend BSS at one of the Hull and East Yorkshire Bowel Cancer Screening centre sites, will be randomly assigned to one of three groups: control (usual care; no input from GP practice), Intervention group A (primer letter/leaflet and a self-referral letter), Intervention group B (primer letter/leaflet and a patient navigation call). Attendance data will be obtained from the BCSP database (via National Health Service (NHS) Digital) 3 months after the last intervention. Regression analysis will compare uptake, and additional clinical outcomes, across the three groups. The analysis will be multivariate and adjust for several covariates including gender and area-level deprivation. Ethics and dissemination: NHS ethical approval has been obtained from London-Harrow Research Ethics Committee. The results will be submitted for publication in a peer-reviewed journal and presented at conferences. Trial registration number: ISRCTN16252122 ; Pre-results.